Tax Implications for the Visiting Professor. - Sommerfeld, Ray M. (The Accounting Review, 1967)
The tax deduction for travel expenses available to a professor who temporarily leaves one U.S. institution to visit a second is an open question of both law and fact. The strongest case for a deduction can be made in those instances where a professor incurs a substantial amount of duplicate costs because of his visiting status and has made a firm commitment to return to his initial employment within a period of less than twelve months. In those cases where a minimum duplication of costs is incurred, the visiting professor should give serious consideration to deducting moving expenses under Sections 62 (8) and 217, rather than traveling expenses under Section 162 (a) (2). Obviously, acceptance of the latter alternative necessitates either (1) giving up the contention that one is away from home or (2) arguing in the alternative. Suffice it to note here that the deduction for moving expenses is limited roughly to the cost of transporting the taxpayer's family, household goods, and personal effects from one location to another, including the cost of meals and lodging while enroute, but not even temporarily after arrival.